Pu-Erh Tea Relaxes the Thoracic Aorta of Rats by Reducing Intracellular Calcium - Luo, Dan; Chen, Xuejiao; Zhu, Xu; Liu, Shuang; Li, Jie; Xu, Jianping; Zhao, Jinhua; Ji, Xu (Frontiers in Pharmacology, 2019)
Previous studies suggested that pu-erh tea aqueous extract could lower blood pressure and ameliorate hypertension symptoms. However, the antihypertension mechanisms of pu-erh tea remain unclear. In this work, the direct effects of pu-erh tea on vessels and cells were investigated by detecting isometric tension and intracellular calcium ([Ca2+]i), respectively. Additionally, to identify the main active components, the aqueous extract of pu-erh was separated by organic solvents to obtain various fractions, and the effects of these fractions on arteries were assessed. The results showed that pu-erh aqueous extract vasodilated rat thoracic aortas preconstricted by phenylephrine or KCl. These vasodilation effects were not significantly affected by the removal of the endothelium or by preincubation with potassium channel blockers (tetraethylammonium, glibenclamide, aminopyridine, or barium chloride). Moreover, pu-erh aqueous extract could reduce the vessel contractibility induced by CaCl2 and phenylephrine under KCl-depolarizing or Ca2+-free buffer conditions, respectively. Furthermore, pu-erh aqueous extract attenuated the KCl-induced increase in [Ca2+]i in cultured rat aortic smooth muscle A7r5 cells. In addition, the chloroform precipitate of pu-erh aqueous extract produced the most potent vasodilation. Theabrownins (the characteristic components of pu-erh tea) accounted for 41.91 ± 1.09 % of the chloroform precipitate and vasodilated arteries in an endothelium-independent manner. In addition, the vasodilation effect of caffeine was verified. In conclusion, theabrownins and caffeine should be the two main active components in pu-erh tea. Pu-erh aqueous extract vasodilated arteries in an endothelium-independent manner, which might partly be attributed to the decrease in extracellular Ca2+ influx. Moreover, our study provided data on the potential mechanism of the hypotensive actions of pu-erh tea, which might improve our understanding of the effect of pu-erh tea on the prevention and treatment of hypertension.